Analisis Faktor Risiko Hipertensi Pada Jemaah Haji Embarkasi Makassar Tahun 1439 H/2018 M - Nur Magfirah (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2020)
Every year around 67 percent of the total pilgrims who go to the holy land in high risk groups. The purpose of this study was to analyze the factors associated with hypertension, including age, sex, type of work, level of education, origin of congregation, knowledge, attitude, diet, smoking habits, lack of exercise habits, and stress levels in Makassar embarkation pilgrimage group in 2018. This research was conducted at the Sudiang Makassar Haji Dormitory. This type of research used cross sectional method. Samples were taken by simple random random sampling until reaching the desired number (consecutive sampling) of 260 people. The results of this study stated that knowledge (p = 0.001) and attitude (p = 0.000) were both significantly associated with reducing the incidence of hypertension, while eating habits, and lack of exercise affected the incidence of hypertension. Conclusions, poor dietary habits and lack of exercise habits are factors that influence the incidence of hypertension in pilgrims. Suggested pilgrims to get used to eating low salt, fat and exercise routine.